Investigation of the relationship between load and loss factors for a Brazilian electric utility - De Oliveira, M. E. [UNESP]; Padilha-Feltrin, A. [UNESP]; Candian, F. J. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
With the considerable increase of the losses in electric utilities of developing countries, such as Brazil, there is an investigation for loss calculation methodologies, considering both technical (inherent of the system) and non-technical (usually associated to the electricity theft) losses. In general, all distribution networks know the load factor, obtained by measuring parameters directly from the network. However, the loss factor, important for the energy loss cost calculation, can only be obtained in a laborious way. Consequently, several formulas have been developed for obtaining the loss factor. Generally, it is used the expression that relates both factors, through the use of a coefficient k. Last reviews introduce a range of factor k within 0.04 - 0.30. In this work, an analysis with real life load curves is presented, determining new values for the coefficient k in a Brazilian electric utility. © 2006 IEEE.
Keywords: constant coefficient k; load curves; load factor; loss factor; A-coefficient; Brazilian electric utilities; Electricity theft; Energy loss; Load curves; Load factors; Loss calculation; Measuring parameters; Developing countries; Electric load loss; Electric utilities; Electric losses